Calon Presiden Perseorangan dan Presidential Threshold dalam Sistem Pemerintahan Presidensial Indonesia - Dirga Achmad; Azlan Thamrin (DIKTUM: Jurnal Syariah dan Hukum, 2021)
The regulations on presidential and vice-presidential candidates can only be proposed through the path of political parties seen as a condition that restricts the people to choose an ideal leader. While the political party that is the focus of hope has experienced a pragmatist disorientation as the holder of the people's mandate. This research is intended to assess the urgency of individual presidential candidates to be accommodated in elections. This research is normative research with conceptual and statutory approaches. The type of data used is secondary data obtained through literature studies which are analyzed qualitatively. The results of this study show that personal presidential candidates and vice-presidents are not very important to be accommodated in the current context, even if there is disorientation of political parties, due to accommodating personal presidential candidates must change the constitutional provisions that are very sacred in the state of Indonesia, because it concerns the lives of many people. Changing the constitution through the fifth amendment of the 1945 NRI Constitution is very inappropriate on the grounds of the lack of constitutional moment and skepticism of political configuration in parliament, so it takes the right time through a substantial comprehensive review to reorganize the state system through amendments to the Constitution. Meanwhile, to pave the way for the availability of many alternative leadership candidates for the people, it is enough to abolish the Presidential Threshold system.